Modernist Projects for Reading the Sunnah of the Prophet: A Review and Criticism of Some of the Literature - Abdullah, Al Harith Fakhry (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2021)
This article examines the literature of modernists who have studied the Sunnah of the Prophet in their books. It attempts to capture modernist criticism and analytical reading of the Sunnah by extracting the premises, methods, tools, goals, and outcomes of their projects. Modernist projects agree in many of their tools and methods, as well as in the approaches used in their critical work; hence, the results are close in their findings, if not exactly the same. The convergence of foundations leads to unity in the outcomes; thus, these projects form one project to a large extent. The article discusses a number of texts chosen because they have not been studied with great care, unlike other works of Arab modernist masters such as Mohammed Arkoun, Nasr Hamid Abu Zayd, Hasan Hanafi, and Muhammad Abid al-Jabiri. On the other hand, each one of the selected works represents a model for applying a tool or method of critical modernism (Hermeneutics, Historicism, or Deconstruction). Likewise, modernists - after contemplation and investigation - share quite a few ideas, perspectives, and critical practices. The literature to be studied in this article was chosen in order to avoid repetition of other studies, although some of them do not represent a self-integrated project as much as they represent a critical practice with modernist tools.